Developing an Industrial Sustainability Strategy Model Through Exploratory Factor Analysis and DEMATEL - Widowati, Tamara Rahma; Sholikha, Nikmatus; Kuswardani, Chintia Dwi Wangsa; Karim, Saifuddin; Pradhani, Nadiyah Larasati (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2026)
Corporate awareness of sustainability has increased significantly alongside growing stakeholder expectations for environmentally responsible practices. The industrial sector’s GDP growth in 2023 was accompanied by higher CO₂ emissions, emphasizing the need for a managerial approach that integrates economic, social, and environmental dimensions. This study develops a strategy map based on the Sustainability Balanced Scorecard (SBSC) by identifying key sustainability performance indicators. Using Exploratory Factor Analysis (EFA), 18 indicators were obtained and grouped into four perspectives: Learning and Growth (3 indicators), Internal Business Processes (8), Stakeholders (3), and Financial (4). The Decision-Making Trial and Evaluation Laboratory (DEMATEL) method was then applied to examine causal relationships. Results highlight “green technology innovation,” “energy efficiency and renewable energy practices,” and “green corporate image” as the most influential indicators. The Internal Business Process perspective was identified as the primary driver of sustainability performance. These findings stress the importance of aligning strategies with operational improvements to achieve balanced economic and environmental outcomes.